Study on synergistic mechanism of PANDAN modification, current and electroactive biofilms on Congo red decolorization in microbial fuel cells. (30th October 2020) - Li, Chao; Luo, Miaomiao; Zhou, Shihua; He, Hanyue; Cao, Jiashun; Luo, Jingyang; Fang, Fang
Abstract: Effect on microbial fuel cells (MFCs) for decolorization of Congo red by Poly (aniline-1, 8-diaminonaphthalene) (PANDAN) modification, current and electroactive biofilms (EABs) is investigated. With the synergism of the three factors: PANDAN modification, current and EABs (A2 reactor), the COD removal and decolorization rate significantly increase to 88% and 97%, as well as the Congo red is thoroughly degraded. The decolorization performance comparison and Redundancy analysis (RDA) results indicate that the EABs take more responsibility (contribute ~ 50%) for the decolorization, rather than the modification and current. Therefore, the effects and mechanism of PANDAN modification and current on EABs are further revealed by the Confocal Scanning Laser Microscopy (CSLM) and high-throughput sequencing analysis. The effects of current (anodic dynamical microenvironment), material adsorption, and electron transfer mediating act comprehensively on the thickness, viability, EPS and microbial community of the EABs, among which the relationship is discussed in depth by hierarchically comparison, with "independent and additional effects". It is demonstrated that the modification, current and EABs present the synergistic effect and promote each other in the performance of the decolorization MFC. Graphical abstract: Image 1 Highlights: Synergism of modification, current and EABs improved MFC's decolorization. EABs played the most important role, with ~50% contribution to the decolorization. Modification, current and EABs presented synergistic effect and promoted each other. Factors as independent or additional led different performance and mechanisms.